A Case of KCNQ2-Associated Movement Disorder Triggered by Fever. (December 2017) - Dhamija, Radhika; Goodkin, Howard P.; Bailey, Russell; Chambers, Chelsea; Brenton, J. Nicholas
The differential diagnosis of fever-induced movement disorders in childhood is broad. Whole exome sequencing has yielded new insights into those cases with a suspected genetic basis. We report the case of an 8-year-old boy with a history of neonatal seizures who presented with near-continuous hyperkinetic movements of his limbs during a febrile illness. Initial diagnostic testing did not explain his abnormalities; however, given the suspicion for a channelopathy, whole exome sequencing was performed and it demonstrated a de novo pathogenic heterozygous variant in KCNQ2 . There is an expanding phenotypic spectrum of heterozygous alterations in KCNQ2 ; however, this report provides the first description of a pathogenic KCNQ2 variant fever-induced hyperkinetic movement disorder in childhood. We also review the literature of cases previously published with the same pathogenic variant.